The impact of international and European legal acts on the example of extradition legislation (Discourse of Law and Administration, 2024)
International legal acts do not in principle prohibit extradition. They regulate and standardize extradition procedures also allow - under certain conditions - the procedures to be prolonged extradition or refusal to extradite the perpetrator. Their impact on the Polish legal system is important because European extradition regulations forced a change to the Constitution of the Republic of Poland.
Keywords: human rights; extradiction; Constitution; Constitutional Court; citizenship